A rare case of incidental chronic ovarian ectopic encountered in a case of ruptured ectopic pregnancy - Pati, Ipsita Priyadarshini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Chronic ectopic pregnancy has mild clinical presentation with absent or subtle symptoms. The high incidence of negative pregnancy tests and a poor specificity of ultrasonography can be misleading, and the correct diagnosis is sometimes established only at the time surgery with its nature or even histopathologically after the operation. Here is the case of chronic ovarian ectopic diagnosed accidentally during the case of ruptured tubal ectopic. 34 years G4P2+1L2 underwent laparoscopic salpingectomy for ruptured tubal ectopic left side. She had a regular menstrual cycle of 24 days and complained of chronic dull aching lower abdomen pain off and on during cycle. Ultrasonography echogenic hemoperitoneum with an anechoic area measuring 19×24.3×23.1 mm with embryo-like echo (18.8 mm in length) amidst the echogenic region. On doing laparoscopy the left ruptured tubal ectopic removed with clearing of hemoperitoneum revealed right bluish black color cyst adherent to adjacent structure forming tubo-ovarian mass. A chronic ectopic pregnancy is often difficult to diagnose due to its subtle symptoms and varied echogencity in ultrasound. It is often mistaken with chronic PID with tubo-ovarian mass or endometrioma.